Integrating traditional crop genetic diversity for mountain food security - Jarvis, D.; Bioversity International; Sthapit, B.R.; Sthapit, S.R. (Bioversity International, 2014)
Introduction brochure to the project 'Integrating Traditional Crop Genetic Diversity into Technology: Using a Biodiversity Portfolio Approach to Buffer against Unpredictable Environmental Change in the Nepal Himalayas'. The project aims to contribute to the conservation of globally important crop biodiversity, which form the basis for food security in areas of high environmental instability and variability in many high-elevation agricultural systems throughout the world. It is implemented by UNEP and executed by Bioversity International, NARC, DoA and LI-BIRD.